Genetic Dissection of Early Blight Resistance in Tetraploid Potato - Xue, Weiya; Haynes, Kathleen G.; Clarke, Christopher R.; Qu, Xinshun (Frontiers in Plant Science, 2022)
Early blight, caused by the fungus Alternaria solani, is one of the most economically important diseases of potatoes worldwide. We previously identified a tetraploid potato clone, B0692-4, which is resistant to early blight. To dissect the genetic basis of early blight resistance in this clone, a full-sib tetraploid potato population including 241 progenies was derived from a cross between B0692-4 and a susceptible cultivar, Harley Blackwell, in this study. The population was evaluated for foliage resistance against early blight in field trials in Pennsylvania in 2018 and 2019 and relative area under the disease progress curve (rAUDPC) was determined. The distribution of rAUDPC ranged from 0.016 to 0.679 in 2018, and from 0.017 to 0.554 in 2019. Broad sense heritability for resistance, as measured as rAUDPC, was estimated as 0.66–0.80. The population was also evaluated for foliar maturity in field trials in Maine in 2018 and 2020. A moderate negative correlation between rAUDPC and foliar maturity was detected in both years. A genetic linkage map covering a length of 1469.34 cM with 9124 SNP markers was used for mapping quantitative trait loci (QTL) for rAUDPC and foliar maturity. In 2018, three QTLs for early blight were detected; two of them on chromosome 5 overlapped with QTLs for maturity, and one of them on chromosome 7 was independent of maturity QTL. In 2019, six QTLs for early blight were detected; two QTLs on chromosome 5 overlapped with QTLs for maturity, and the other four QTLs did not overlap with QTLs for maturity. The identification of these QTLs provides new insight into the genetic basis of early blight resistance and may serve as sources for marker-assisted selection for early blight resistance breeding.